“Community health workers bring value and deserve to be valued too:” Key considerations in improving CHW career advancement opportunities - Smithwick, Julie; Nance, Jenesha; Covington-Kolb, Sarah; Rodriguez, Ashley; Young, Mike (Frontiers in Public Health, 2023)
The BPC worked to draft examples of tiered CHW job descriptions, based on the different requirements for the position. The Council also recommended that, statewide, there should be multiple tiers of CHW certification, and that additional CHW-focused education and experience should be what help move a CHW from one tier to the next. Community Health Workers (CHWs) are a critical part of the public health workforce, who connect the communities they serve with resources, advocate for communities facing health and racial inequities, and improve quality of healthcare. However, there are limited professional and career building pathways for CHWs, which contributes to low salaries and lack of career advancement, further resulting in turnover, attrition and workforce instability. The Center for Community Health Alignment (CCHA) within the University of South Carolina, utilized a mixed-method data collection strategy to provide a more in-depth understanding of this issue and ways that employers, advocates and CHWs can address it . Utilizing input from experienced CHWs and CHW allies nationally, this paper describes the importance of supporting CHW career advancement, and shares best practices and suggestions for designing strategies that organizations can use to improve CHW career pathways and reduce attrition.